I can't wait! Neural reward signals in impulsive individuals exaggerate the difference between immediate and future rewards. (12th November 2016) - Schmidt, Barbara; Holroyd, Clay B.; Debener, Stefan; Hewig, Johannes
Abstract: Waiting for rewards is difficult, and highly impulsive individuals with low self‐control have an especially hard time with it. Here, we investigated whether neural responses to rewards in a delayed gratification task predict impulsivity and self‐control. The EEG was recorded from participants engaged in a guessing game in which on each trial they could win either a large or small reward, paid either now or after 6 months. Ratings confirmed that participants preferred immediate, large rewards over small, delayed rewards. Electrophysiological reward signals reflecting the difference between immediate and future rewards predicted self‐report measures of impulsivity and self‐control. Further, these signals were highly reliable across two sessions over a 1‐week interval, showing high temporal stability like stable personality traits. These results suggest that greater valuation of immediate rewards causes impulsive individuals to redirect control away from delayed rewards, indicating why it is so hard for them to wait.